(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article deals with the state and relevance of conducting philosophical research in Kyrgyzstan in the Kyrgyz language. Using the example of the actions of Al-Farabi and Hegel to conduct research on philosophy in their ethnic languages, separate concepts of the dialectic of language and philosophy are analyzed.